Texas Myths and Legends : the True Stories behind History's Mysteries. - Ingham, Donna (Legends of the West., 2016)
Each episode included in this book explores unusual phenomena, strange events, and mysteries in Texas's history. From rumors of Jean Lafitte's buried treasures to the hanging of Chipita Rodriguez and the love story of Frenchy McCormick, Texas Myths and Legends makes history fun and pulls back the curtain on some of the state's most fascinating and compelling stories.